(untitled) (Journal of the College of Basic Education, 2022)
The research included five chapters. The first chapter contained the introduction of the research and its importance is reflected in the analysis of the types of preparation for the matches of some Arab teams to give a clear picture to the coach and the players about the level of their performance and the relationship of that performance to the effectiveness of crushing hitting and the arrangement of the teams and to know the strengths and weaknesses to invest and focus on them, which is what the researchers considered a problem that must be Paying attention to it, the descriptive approach was used in the manner of studying the correlational relationships to find the objectives of the research, which are: